Omni-channel evolution: confronting the whats and hows - Saghiri, Soroosh; Bourlakis, Michael (Emerald, 2020)
Retail supply chains are experiencing a fast-forward evolution, surrounded by increasing technology motivations, market expectations and business environment uncertainties. Online retail and electronic commerce are not market winners any more, and the question for many retailers is not about “to be or not be” visible and active in multiple channels, but more concerning on how to be efficient and effective using a seamless omni-channel retail solutions